Estimation of density and fracture orientation in HTI media through azimuthal analysis of p-waves - Montes Vides, Luis Alfredo; Cortes Gómez, Diana Marcela; Agudelo Zambrano, William Mauricio (CT&F - Ciencia, Tecnología y Futuro, 2013)
In a medium with Horizontal Transverse Isotropy (HTI) associated with fractures, Normal Move Out (NMO) velocity varies ellipsoidally with the azimuth. The major axis of the ellipse indicates the direction of the fractures. Also, density is defined by the axial ratio. We are presenting a methodology to estimate fracture parameters based on the difference of NMO times measured in two orthogonal common midpoint seismic lines. The method was tested with synthetic data and then applied in seismic data of the La Luna Formation in the Tenerife Field, providing the orientation of the fractures as well as an estimated density. Results were validated by analysis of Fullbore Formation Microimager FMI logs acquired in wells in the vicinity of the Field.